Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Students’ Attitudes at UNRWA's University College for Educational Sciences in Palestine Toward Electronic Tests from their own Points of ViewDr. Jamal Mohammad Marshood , Mrs. Iman Mostafa Hamoda , Mrs. Duha Sami Mufreh , Mrs. Fatin Adel Ayyash , Mrs. Nujood Ayed Hamduni2. The role of university administration in spreading the entrepreneurship culture among students of Prince Satam bin Abdulaziz University and the obstacles to activating it from the viewpoint of the university administrationMrs. Amal Farhan Nasser Al-Dosari , Dr. Abdul Aziz Muhammad Al-Saqer3. Territorial Governance and Competencies of Managing the Territory in the Moroccan Primary Education CurriculumMrs. Rachida Allal AOUIDATE, Prof. Mustapha AAFIR , Prof. Abd Elouahed Boubria4. The Extent to which Teachers of Deaf and Hard of Hearing Students in the Primary Stage use Augmented Reality Applications and the Barriers they FaceMr. Mohammed Saleh Alghamdi, Dr. Turki Samah Alzahraney5. The Role of Sustainable Leadership in Achieving Professional Motivation at the Education Offices in RiyadhMrs. Bayan Saud Al-Zaid6. Methods of coping with stress and its relationship to the quality of family life to a sample of mothers of deaf and hard of hearing children in the western region of the Kingdom of Saudi ArabiaMrs. Dhuha Omar Almaghrabi7. Impact of a collective mentorship programmer on reducing depression and improving the self-esteem of Syrian female students in the Za 'atari campMrs. Na'ela Odeh Abedalqader Keelani
Keywords: Journal of Educational and Psychological Sciences